Electron scattering in large water clusters from photoelectron imaging with high harmonic radiation. Issue 24 (6th June 2018) - Gartmann, Thomas E.; Hartweg, Sebastian; Ban, Loren; Chasovskikh, Egor; Yoder, Bruce L.; Signorell, Ruth
Abstract : The scattering of low kinetic energy electrons in large water clusters can be treated as an intermediate case between gas and condensed phase scattering. Abstract : Low-energy electron scattering in water clusters (H2 O) n with average cluster sizes of 〈 n 〉 < 700 is investigated by angle-resolved photoelectron spectroscopy using high harmonic radiation at photon energies of 14.0, 20.3, and 26.5 eV for ionization from the three outermost valence orbitals. The measurements probe the evolution of the photoelectron anisotropy parameter β as a function of cluster size. A remarkably steep decrease of β with increasing cluster size is observed, which for the largest clusters reaches liquid bulk values. Detailed electron scattering calculations reveal that neither gas nor condensed phase scattering can explain the cluster data. Qualitative agreement between experiment and simulations is obtained with scattering calculations that treat cluster scattering as an intermediate case between gas and condensed phase scattering.